Biochar-Based Catalysts : Preparation, Characterization and Applications - Showkat, Ahmad Bhawani (Springer Nature Singapore Pte Ltd, 2024)
This book reviews comprehensively the field and development of biochar-based catalyst by summarizing fundamental approaches and principles to prepare biochar and biochar-based catalysts and focusing on the main applications of biochar-based catalysts in environmental remediation. Biochar is a low-cost carbonaceous material produced from biomass and is regarded as an economical substitute to the activated carbon. The coverage of book highlights the most exciting applications of biochar-based catalysts in different reactions such as oxidation, reduction, hydrolysis, isomerization, dehydration, etc. The book is useful for the academics and researchers who are interested in the development biochar-based catalysts with background in material science, chemical engineering, environmental engineering and environmental chemistry.